Pseudoaneurysm of profunda femoris artery following internal fixation of intertrochanteric fracture: Two cases report - Anupong Laohapoonrungsee (2018)
The authors report two cases of an uncommon but preventable complication after fixation of intertrochanteric hip fracture, the pseudoaneurysm of the profunda femoris artery. Both cases in the present study presented as proximal thigh mass, and soft tissue sarcoma was suspicious in one case. The diagnosis was confirmed by angiographic study and the feeding vessels were successfully occluded during angiography. Proper placement of the retractors, using a shorter drill or drill guard, accurate screw length and a shorter side-plate DHS were recommended to prevent this problem.